Tools of the Trade: An Exploratory Study Analyzing the Frequency and Potency of Tools in Hip-Hop Music Creation, Performance, and Pedagogy - Drew X Coles; Cato Zane (Journal of the Association for Technology in Music Instruction, 2025)
This paper presents findings from a qualitative research study examining the tools most frequently used in the creation, performance, and teaching of hip-hop music. The study collected data from three key stakeholder groups: professional practitioners, music educators, and amateur creators. Through thematic analysis, the research identifies tools ranging from hardware such as MIDI controllers and turntables to software like DAWs and mobile apps, and explores their perceived effectiveness in facilitating musical creativity. The study’s goal is to inform music educators about the tools that dominate the hip-hop marketplace and their various applications. By understanding how different tools contribute to beat-making, sampling, lyrical composition, and live performance, educators can more effectively align their teaching practices with industry trends. Special attention is given to equity in access to music technology, highlighting how low-cost and open-source tools bridge socioeconomic gaps for aspiring creators.